IMPLEMENTATION OF RELIGIOUS MODERATION IN THE DEVELOPMENT OF A SHARI'AH ECONOMIC AND FINANCIAL SYSTEM THAT IS FAIR FOR SOCIETY - Iwan Setiawan; Rahayu Kusumadewi; Nurhaeti; Dimas Hardiansyah (Gunung Djati Conference Series, 2024)
This research aims to analyze the application of religious moderation in a sharia economic and financial system that is fair to society. This research includes library research with qualitative research methods that use a descriptive approach. The results of this research reveal that the concept of religious moderation has been fully implemented in the development of the Sharia Financial Institution (LKS) system, through openness regarding the use of LKS which is not only specifically for Muslim customers but also for customers of other religions. However, regarding the placement of Human Resources (HR) in LKS who come from non-Muslim communities, this has not received special attention. Apart from that, it is necessary to formulate derivative regulations as a legal umbrella that gives non-Muslims the same rights to become employees at LKS. The granting of these rights must of course fulfill the terms and conditions that apply to the application of sharia principles in all LKS operations. Thus, granting the same rights to non-Muslim communities as part of LKS human resources will create a sharia economic and financial system that is just for society.